(3LhGgQ GdbQGf hOQQgs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3GYde Cf hGVY gPG GdcJGH SeGg LhGgQ GdbQBf hOQQg hQJHg Ydi KdGKI CbSGe s
(3BNQgG (B:s
(3aYdjc Cf JOje GdacQ ai gPjf GdfeWjf aHPdc JfGd ZGjGJ GdSYGOGJ hGdMeO ddg QH GdYGdejf s
(3cJHJ Hdhfjf ef EYOGO CMOge CShO cGf XGgQkG CeG GdBNQ adjS XGgQ aXgQJ ai GdfSNI CeGcf cKjQI HgG HjGVs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI eTgO (B- (3cdjI GdEdgjGJ (B(123) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs